Implementation of the Integrated Management of Childhood Illnesses strategy in Northeastern Brazil - Amaral, João Joaquim Freitas do; Victora, Cesar Gomes; Leite, Álvaro Jorge Madeiro; Cunha, Antonio José Ledo Alves da (Revista de Saúde Pública, 2008)
OBJECTIVE: The majority of child deaths are avoidable. The Integrated Management of Childhood Illnesses strategy, developed by the World Health Organization and the United Nations Children's Fund, aims to reduce child mortality by means of actions to improve performance of health professionals, the health system organization, and family and community practices. The article aimed to describe factors associated with the implementation of this strategy in three states of Northeastern Brazil. METHODS: Ecological study conducted in 443 municipalities in the states of Northeastern Brazil Ceará, Paraíba and Pernambuco, in 2006. The distribution of economic, geographic, environmental, nutritional, health service organization, and child mortality independent variables were compared between municipalities with and without the strategy. These factors were assessed by means of a hierarchical model, where Poisson regression was used to calculate the prevalence ratios, after adjustment of confounding factors. RESULTS: A total of 54% of the municipalities studied had the strategy: in the state of Ceará, 65 had it and 43 did not have it; in the state of Paraíba, 27 had it and 21 did not have it; and in the state of Pernambuco, 147 had it and 140 did not have it. After controlling for confounding factors, the following variables were found to be significantly associated with the absence of the strategy: lower human development index, smaller population, and greater distance from the capital. CONCLUSIONS: There was inequality in the development of the strategy, as municipalities with a higher risk to child health showed lower rates of implementation of actions. Health policies are necessary to help this strategy to be consolidated in the municipalities that are at a higher risk of child mortality.